The choice of material for strengthening of leading edges of working blades of steam turbines - Hlushkova, D.B.; Hrinchenko, O.D.; Kostina, L.L.; Cholodov, A.P. (Вопросы атомной науки и техники, 2018)
Research on the state of strengthened layer of working blades of steam turbines made by electrospark doping with T15K6 alloy and 15X11МФ-Ш steel is commissioned. Microstructure, microhardness and thickness of weld pad are studied. The possibility of 15X11МФ-Ш steel using for hardening of leading edges of working blades of steam turbines is substantiated.